Mapping the University of Washington Quality of life questionnaire onto EQ‐5D and HUI‐3 indices in patients with head and neck cancer. Issue 3 (24th November 2019) - Stephens, Robert F.; Noel, Christopher W.; Su, Jie (Susie); Xu, Wei; Krahn, Murray; Monteiro, Eric; Goldstein, David P.; Giuliani, Meredith; Hansen, Aaron R.; de Almeida, John R.
Abstract: Background: There is no mechanism to predict health utility (HU) values from the University of Washington Quality of Life Questionnaire (UWQoL) scores. We sought to develop a mapping algorithm capable of using UWQoL data to approximate HU scores. Methods: Outpatients with head and neck cancer completed the UWQoL, EQ‐5D, and the Health Utilities Index‐Mark 3 (HUI‐3). Results of the UWQoL were mapped onto both EQ‐5D and HUI‐3 scores using ordinary least‐squares regression models. Two‐part models were explored. The predictive power of the model was assessed using 10‐fold cross‐validation. Results: A total of 209 patients were recruited. The reduced model converting UWQoL data into EQ‐5D scores performed best (adjusted R 2 = 0.628, root mean square error = 0.076). Both models demonstrated construct validity by discriminating between clinical indices of disease severity. Conclusions: The abovementioned algorithms enable researchers to perform health economic evaluations with existing UWQoL data in cases where prospectively collected HU values are not available.